THE USE OF BUZZWORD WRITING TECHNIQUE TO IMPROVE STUDENTS’ WRITING ABILITY AT THE FIRST SEMESTER OF STKIP YPUP - HB, Lukman; Halim, Nurfitriyah; Fitriani, Fitriani (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research was to find out whether the use of Buzzword writing technique to improve students writing ability at the first semester of STKIP-YPUP Makassar. The method used in this research was a pre-experimental using one group pre-test and post-test. This population of this research was the first semester of STKIP-YPUP Makassar which consist of one class was one classroom, the total population was 35 students. The researcher applied a random sampling technique by taking the first semester. To collect data, the researcher used an instrument, namely writing test. It will be used in pre-test and post-test. The test questions consisted of 10 items, they were 10 multiple choice buzzwords and 10 fill in the blank questions. The students’ post-test was higher than the students’ pre-test (85 > 33.66). The T-Test was higher than the T-Table (27.659 > 2.144). Based on the data analysis, it can be concluded that Buzzword Writing Technique improves the students’ writing ability.